Self-Medication Practice among Medical Students of a Tertiary Teaching Hospital in Dhaka City - Khan, Asma; Sultana, Afroza; Ahammad, Benzir; Nahar, Shamsun; Khanam, Shafeya (Journal of Current and Advance Medical Research, 2019)
Background: Self-medication is a common practice worldwide and the irrational use of drugs is a cause of concern. Objective: This present study was designed to assess the rate of self-medication among the medical students in a tertiary teaching hospital in Dhaka. Methodology: This descriptive cross-sectional study was conducted in the Department of Pharmacology at Shaheed Suhrawardy Medical College, Dhaka, Bangladesh from October to December 2017 for a period of three (03) months. The participants were briefed about the nature of the study; the consent was taken and a pre‐tested semi‐structured questionnaire was administered to them. The information pertaining to the pattern of self‐medication, indications for self‐medication and drugs used for self‐medication was included in the questionnaire. Result: A total of 303 students were included in this study. The rate of self-medication was 100.0%. A larger number of females were self-medicating (81.2%) than males (75.3%). The majority of the students self-medicated because of the illness being too trivial for consultation (43.2%) and previous experience of illness (43.2%). Fever (73.3%) and headache (65%) are the most common cause of self-medication. Antipyretics were most commonly self–medicated by the participants (98%). 45.5% 0f students told that self-medication is not an acceptable practice. 40% of the participants opined that self-medication was a part of self-care. Conclusion: In conclusion self-medication is widely practiced among students of the institute Journal of Current and Advance Medical Research 2019;6(1):28-31